Mineralogy of Noble Metals and "Invisible" Speciations of These Elements in Natural Systems - Palyanova, Galina (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue covers a broad range of topics related to the mineralogy of noble metals (Au, Ag, Pt, Pd, Rh, and Ru) and the occurrence, formation, and distribution of these elements in natural ore-forming systems. This collection of eleven research articles discusses various problems related to these topics. I hope this Special Issue will contribute to a better understanding of the genesis of gold, silver, and other noble metal deposits as well as the behavior of these elements in endogenic and supergene environments, and suggest ways forward to solving the problem of their full extraction from ores.